2021
DOI: 10.3390/antiox11010068
|View full text |Cite
|
Sign up to set email alerts
|

Towards Functional Insect Feeds: Agri-Food By-Products Enriched with Post-Distillation Residues of Medicinal Aromatic Plants in Tenebrio molitor (Coleoptera: Tenebrionidae) Breeding

Abstract: Sustainability, circular economy and alternative production systems are urgent imperatives for humanity and animal husbandry. Unless wasted, agri-food by-products can offer a promising source of high value. We evaluated the effect of rice bran (RB), corncob (CC), potato peels (PP), solid biogas residues (BR), and olive-oil processing residuals (OR), as alternative substrates to wheat bran (WB as control), on the growth and nutritional value of Tenebrio molitor during its breeding for animal feeds and/or human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 87 publications
3
19
0
Order By: Relevance
“…Simultaneously, insects’ mass production can fit well with the circular economy model, which embraces the continual and efficient recycling and reuse of materials, by-products or wastes as resources in an effort to minimize waste generation [ 10 ]. Insects’ production may exploit several low-value organic, industrial and agricultural by-products as rearing substrates which insects can efficiently be recycled and bioconverted into high-value protein [ 8 , 11 , 12 ]. In particular, recent studies demonstrated that by-product substrates may increase the final weight and enhance the antioxidant capacity of insects [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Simultaneously, insects’ mass production can fit well with the circular economy model, which embraces the continual and efficient recycling and reuse of materials, by-products or wastes as resources in an effort to minimize waste generation [ 10 ]. Insects’ production may exploit several low-value organic, industrial and agricultural by-products as rearing substrates which insects can efficiently be recycled and bioconverted into high-value protein [ 8 , 11 , 12 ]. In particular, recent studies demonstrated that by-product substrates may increase the final weight and enhance the antioxidant capacity of insects [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Insects’ production may exploit several low-value organic, industrial and agricultural by-products as rearing substrates which insects can efficiently be recycled and bioconverted into high-value protein [ 8 , 11 , 12 ]. In particular, recent studies demonstrated that by-product substrates may increase the final weight and enhance the antioxidant capacity of insects [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding can offer a convincing point for consumers to accept the use of insect‐based feed in duck diets, as shown previously, as the inclusion of insect‐based feeds can result in meat with higher levels of phenols, flavonoids, essential oils, and antioxidants compared with their control groups (Andreadis et al . 2022; Van Huis 2022). Moreover, the breast meat color values of ducks were not affected ( p > 0.05) by increasing levels of pelleted PT, except for lightness (L* values) on day 7 and yellowness (b* values) on day 3 ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…When residues of medical aromatic plants (lavender, Greek oregano, rosemary, olive) were supplemented to rice bran and corn cob as substrates to feed yellow mealworm, its growth and antioxidant activity increased (Andreadis et al . 2022).…”
Section: Processing Into Insect Productsmentioning
confidence: 99%